National Health Management Information System: Issues of Funding and Support - Akinde, A. D.; Soriyan, H. A.; Makanjuola, R. O. A. (Methods of Information in Medicine, 1997)
Information Technology has made a substantial inroad into Nigerian society, particularly since the late 1980s. It is, however, already being applied in the health sector.The Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC), Ile-Ife, Nigeria has adopted a systematic approach to the development of a Health Information System (HIS) for a typical specialist hospital. A review of the existing HIS in OAUIHC is presented, highlighting its attributes, problems, and limitations. In addition, the options of funding HIS on a national scale are identified and discussed.Finally, strategies to ensure ongoing support of a national HIS are presented.
Keywords: Health Information Systems; Developing Countries